1998
DOI: 10.1029/97tc03025
|View full text |Cite
|
Sign up to set email alerts
|

Shallow structure of the Yadong‐Gulu rift, southern Tibet, from refraction analysis of Project INDEPTH common midpoint data

Abstract: Metamorphic minerals within the shear zones indicate at least amphibolite grade metamorphism with increasing metamorphic grade down section. The seismic data, coupled with the new geologic information and geomorphologic data from Landsat imagery, suggest that the structure of the northern YadongGulu rift is comparable to other well-documented rift systems in which steep range-front normal faults terminate at, or sole into, moderately dipping normal-sense detachments at depth that have undergone substantial foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 37 publications
5
64
0
Order By: Relevance
“…At the scale of the East African Rift, some segments display similar features (Keranen et al 2009;Tuluka 2010;Wölbern et al 2010;Gummert et al 2015), and more generally low-velocity crustal zones are observed for similar depth in other rifts, such as the Rhine graben (Fuchs et al 1987), Southern Tibet (Cogan et al 1998;Jiang et al 2014) and the Baikal Rift (Mordvinova et al 2007;Basuyau & Tiberi 2011). In most cases, this pattern is attributed to multiple deep processes or features such as partial melting, magmatic chambers, aqueous fluids or even crustal delamination (e.g.…”
Section: Breaking Up a Thick Crustmentioning
confidence: 96%
“…At the scale of the East African Rift, some segments display similar features (Keranen et al 2009;Tuluka 2010;Wölbern et al 2010;Gummert et al 2015), and more generally low-velocity crustal zones are observed for similar depth in other rifts, such as the Rhine graben (Fuchs et al 1987), Southern Tibet (Cogan et al 1998;Jiang et al 2014) and the Baikal Rift (Mordvinova et al 2007;Basuyau & Tiberi 2011). In most cases, this pattern is attributed to multiple deep processes or features such as partial melting, magmatic chambers, aqueous fluids or even crustal delamination (e.g.…”
Section: Breaking Up a Thick Crustmentioning
confidence: 96%
“…The STDS separating these two tectonostratigraphic units is exposed on top of the steep south facing cliffs of the Table Mountains at Gansser [1983], Cogan et al [1998], Grujic et al [1996], Burg and Chen [1984], Burchfiel et al [1992], and Edwards et al [1999]. Seismotectonic Goalpara lineament after De and Kayal [2003].…”
Section: Geological Setting In Eastern Lunanamentioning
confidence: 99%
“…The first is the STDS [Burg and Chen, 1984;Burchfiel et al, 1992], a system of shallowly north dipping normal faults, which acted contemporaneously with the Main Central Thrust during the Miocene southward extrusion of the HHC. The second type comprises ESE-WNW directed extension of the Tibetan Plateau and resulted in both normal faulting (N-S trending rift systems) and NW-SE and NE-SW oriented conjugate strike-slip faulting (Figure 1) [Armijo et al, 1986[Armijo et al, , 1989Fielding et al, 1994;Cogan et al, 1998]. Seismic moment tensors for earthquakes within northern and central Tibet suggest that ESE-WNW extensional strain dominates active deformation of the plateau interior, [e.g., Molnar and LyonCaen, 1989;Langin et al, 2003, and references cited therein] which causes an eastward movement of crustal material out of India's path.…”
Section: Introductionmentioning
confidence: 99%
“…The location of 90.40°E 29.72°N determined by the China Earthquake Administration (CEA) preliminary field survey suggests that the earthquake occurred on the Southeastern Piedmont of the Nyainqentanglha Mountains (SPNM), which borders the northwest side of the northern YadongGulu rift (COGAN et al, 1998) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Because the N-S trending grabens and half grabens constitute direct evidence for Neogene/Quaternary extension of the Tibetan Plateau (ARMIJO et al, , 1989, the easily accessed Yadong-Gulu rift at approximately 90°E longitude is the most intensively studied (COGAN et al,1998). CHEN et al, (2004) used 45 GPS sites to estimate the extension rate of the Yadong-Gulu rift as 5.9 ± 0.7 mm/year in the N69°W direction, much higher than that of 1.4 ± 0.8 mm/year inferred by ARMIJO et al, (1986).…”
Section: Introductionmentioning
confidence: 99%